2020
DOI: 10.1097/fbp.0000000000000562
|View full text |Cite
|
Sign up to set email alerts
|

Repeated nicotine vapor inhalation induces behavioral sensitization in male and female C57BL/6 mice

Abstract: Electronic cigarette use has significantly increased over the past decade. However, there is limited preclinical research on the behavioral and abuse-related effects of nicotine vapor inhalation in rodents. The present study evaluates the effects of repeated nicotine vapor inhalation in male and female mice using a nicotine behavioral sensitization model. Male and female C57BL/6 mice were administered vaporized nicotine (0–10.0 mg/ml) or the positive control of intraperitoneally administered nicotine (0.5 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…Repeated exposure to nicotine produced a robust behavioral sensitization, which is in agreement with previous studies ( Benwell and Balfour, 1992 ; Ericson et al, 2010 ; Hamilton et al, 2014 ; Morud et al, 2016 ; Honeycutt et al, 2020 ). Behavioral sensitization to repeated psychostimulant administration has been proposed to reflect many of the neurochemical changes that are characteristic for drug addiction ( Robinson and Berridge, 1993 ; Steketee and Kalivas, 2011 ), and is in this regard a well-established model to outline behavioral transformations elicited by drugs of abuse.…”
Section: Discussionsupporting
confidence: 92%
“…Repeated exposure to nicotine produced a robust behavioral sensitization, which is in agreement with previous studies ( Benwell and Balfour, 1992 ; Ericson et al, 2010 ; Hamilton et al, 2014 ; Morud et al, 2016 ; Honeycutt et al, 2020 ). Behavioral sensitization to repeated psychostimulant administration has been proposed to reflect many of the neurochemical changes that are characteristic for drug addiction ( Robinson and Berridge, 1993 ; Steketee and Kalivas, 2011 ), and is in this regard a well-established model to outline behavioral transformations elicited by drugs of abuse.…”
Section: Discussionsupporting
confidence: 92%
“…We have shown that the inhalation of nicotine vapor increases spontaneous locomotor activity and decreases body temperature in male Sprague-Dawley rats, while reductions in activity were observed after nicotine injection (0.4, 0.8 mg/kg, s.c.) (Javadi-Paydar et al 2019a; Javadi-Paydar et al 2019b), similar effects have been reported in mice (Honeycutt et al 2020). Increased activity was found after 15 or 30 minutes of nicotine inhalation (30 mg/mL in the propylene glycol vehicle) in the male rats, lasted only ∼15-30 minutes after vapor exposure and were blocked by pre-inhalation administration of the nicotinic acetylcholine receptor (nAChR) antagonist mecamylamine (Javadi-Paydar et al 2019b).…”
Section: Introductionsupporting
confidence: 85%
“…This is likely because mecamylamine itself reduced body temperature in the absence of nicotine here and in prior studies (Hetzler and Bauer 2013). The additive effect on lowering body temperature has also been reported in mice treated with mecamylamine prior to nicotine vapor inhalation (Honeycutt et al 2020).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Importantly, varying patterns of nicotine-induced locomotion can become more prevalent once sex as a biological variable is considered. For example, many studies report increased behavioral activation over time in females when compared to males (Booze et al, 1999; Hamilton et al, 2014), but others report similar behavior between sexes (Ericson et al, 2010; Honeycutt et al, 2020). Further, locomotor activation reaches a maximum at moderate doses of nicotine, and high doses of nicotine induces low locomotion for both sexes (Elliott et al, 2004).…”
Section: Introductionmentioning
confidence: 99%